Anti-VEGF Therapy for Retinal Vein Occlusions - Campa, Claudio; Alivernini, Giuseppe; Bolletta, Elena; Parodi, Maurizio B.; Perri, Paolo (Current Drug Targets, 2016)
Retinal vein occlusion (RVO) is the second most common cause of visual loss in the Western World. RVO is usually classified into branch RVO (BRVO) and central RVO (CRVO) according to the anatomical site of the vascular occlusion. The pathogenesis of RVO is not yet fully understood, however an important event is the intraluminal thrombus formation, which is usually secondary to several conditions such as hypertension, hyperlipidemia, diabetes and thrombophilia. The blockage of venous circulation causes an elevation of intraluminal pressure in the capillaries, leading to hemorrhages and leakage of fluid within the retina, increase of interstitial pressure and a consequent reduction of retinal perfusion. Ischemia may develop resulting in secretion of vascular endothelial growth factor (VEGF) that causes further vascular leakage and retinal oedema. VEGF has therefore a leading role in RVO pathogenesis and symptoms. As a consequence use of anti-VEGF agents by intravitreal injections has become very common with the aim to improve the clinical outcomes in these patients. Currently 2 anti-VEGF agents (ranimizumab and aflibercept) have been FDA (Food and Drug Administration) and EMA (European Medicine Agency) approved for the treatment of RVO, while another VEGF inhibitor (bevacizumab) is often used “off-label” in clinical practice. Many treatment regimens have been suggested in the clinical trials with these drugs, as monthly injections or injections when needed, however the ideal regimen has not been defined yet. We conducted a systematic review searching MEDLINE for the following terms: retinal vein occlusion, ranibizumab, bevacizumab, aflibercept, vascular endothelial growth factor, macular oedema. Data were extracted by one author (AG and BE) and checked by a second (BPM, CC). Aim of this article was to review available data for each drug, focusing on their efficacy and safety trying to compare their advantages and limits.
Keywords: Aflibercept